ANALISIS SPASIAL KASUS TUBERKULOSIS DI KELURAHAN MUKTIHARJO KIDUL TAHUN 2021-2023 - Maulani, Nuraulia; Wulandari, Fitria; Hartini, Eko; Aryani, Lenci (VISIKES, 2025)
Tuberculosis is one of the ten main diseases that cause death throughout the world. In 2021 there were 51 cases recorded, there was a significant decrease in 2022 to 30 cases, and until October 2023, there were 26 cases of Tuberculosis recorded in Muktiharjo Kidul Village. This research aims to carry out spatial analysis and statistical tests on Tuberculosis cases based on population risk factors and housing conditions in Muktiharjo Kidul Village during the 2021- 2023 period. This research approach is descriptive quantitative using a spatial analysis model and relying on secondary data. Case mapping was carried out using the Geographic Information System (GIS) application. The results of this research are presented through mapping the distribution of Tuberculosis cases using GIS technology. The conclusion of the research shows that the distribution of Tuberculosis cases tends to be concentrated in areas with moderate population density, while the homes of Tuberculosis sufferers have room temperatures that do not meet standards.